POLITENESS STRATEGIES IN DELIVERING ULOS IN TOBA BATAK WEDDING CEREMONY - SARINA KIKI SIANTURI; I Wy Dirgeyasa; Fauziah Khairani Lubis (LINGUISTICA, 2021)
This study was aimed atinvestigating the politeness strategies used in delivering ulos in Toba Batak wedding ceremony. The research was conducted by using descriptive qualitative research to analyze and identify the politeness strategies used in delivering ulos in Toba Batak wedding ceremony.The data were taken from the conversation of Toba Batak wedding ceremony of Omry Retno Simangunsong, S.Sos & Triana Puspita Sari Br. Hutabarat, Amd.Keb (21th September 2019), that were held in Wisma Tiberias located at Jl. Pematang Siantar Kecamatan Lubuk Pakam. The findings of the study showed that three politeness strategies found during delivering ulos in Toba Batak wedding ceremony, namely: Bald on Record, Positive Politeness and Negative Politeness, specifically, 15 (60%) for Bald on Record Strategy, 9 (36%) for Positive Politeness, 1 (4%) for Negative Politeness. Off Record was not found during delivering ulos in Toba Batak wedding ceremony. The most dominant types of politeness strategies in delivering ulos in Toba Batak wedding ceremony were Bald on Record.Toba Batak speakers seldom applied negative politeness to avoid social distance or awkwardness in the situation. In Toba Batak wedding ceremony, to utter some speech acts, bride’s kin and bridegroom’ kin use some address forms as symbol of honor